Réponses

2013-12-04T23:56:29+01:00
1)
a= 3^4 x2^5 x 5^6 / 3^7 x 2^9 x 5^3 = 3^-3 x2^4 5^3 = 2^4 x5^3/ 3^3 =16 x 125 / 27 = 2000/27 = 2 x 10^3/3^3
b = 7^12 x9^12x5^-5 / 9^10 x5^-42 x7^-17 = 7^29 x 9^2 x 5^37
c = (-4)7 x 4^11 x (-6)^2 x6^3 x 3^-7 x (-3)^-5 = 4^18 x 6^5  x - (3^12)
d = ((3^9)^2 x 5^7 / 5^-8 x2^9 x3^19 )^3 =( 3^18 x 3^-19 x 5^7 x 5^8 x 2^-9) ^3 =
(3^-1 x 5^15 x 2^-9)^3 = 3^-3 x 5^45 x 2^-27
2)
a= 8^7 x 10^9/ 8^5 x 10^2 = 8^7 x8^-5 x10^9 x 10^-2 = 8^2 x 10^7
b= 6^5 x (7^2)^2 x 10^-7 x 10^7 x 3^-4 x 7^-2 x 2^-4 = 2^5 x 2^-4 x 3^5 x 3^-4 x 7^4 x 7^-2 = 2 x 3 x 7^2 = 6 x 7^2 

c = 2,5^3 x 6^4 x 4^3 x 3^4 x 5^-9 x 9^-2 x 2^-11 = 2.5^3 x 2^4 x 2^-11 x 3^4 x 3^4 x 4^3 x 2 ^-9 x 2.5^-9 x 9^-2 = 2.5 ^-7 x 2^-10 x 3^8 x 3^-6 = 2.5^-7 x 2^-10 x 3^2
merci beaucoup
oups, le dernier
D= 2^4 x3^2 / 10^22 = 2^4 x2^-22 x5^22x3^2 = 2^-18 x 5^22 x 3^2